KEPERCAYAAN-EL (E-TRUST) MAHASISWI-PEKERJA DI TANGERANG SELATAN TERHADAP NIAGA-EL SHOPEE - Chandra Arifianto; Yuli Pratiwi (DAS Institute, 2021)
This study examines perceived electronic Service Quality (PeSQ) and e-Satisfaction concerning e-Trust in Shopee e-commerce. The population in this study was all student-workers at Pamulang University, who were Shopee users with 149 respondents. This study uses a quantitative descriptive method with non-probability sampling, simple regression analysis, and multiple regression analysis using the SPSS program. The results of this study indicate that Perceived electronic Service Quality (PeSQ) and e-Satisfaction have a positive and significant influence on student-worker e-Trust, either partially or simultaneously.